Some remarks on the fractional Sumudu transform and applications - Kilicman, Adem; Altun, Omer (Natural Sciences Publishing, 2014)
In this work we study fractional order Sumudu transform. In the development of the definition we use fractional analysis based on the modified Riemann - Liouville derivative, then we name the fractional Sumudu transform. We also establish a relationship between fractional Laplace and Sumudu via duality with complex inversion formula for fractional Sumudu transform and apply new definition to solve fractional differential equations.